Plasma performance improvement with favourable Bt relative to unfavourable Bt in RF-heated H-mode plasmas in EAST. (12th January 2021) - Lin, X.; Yang, Q.Q.; Xu, G.S.; Huang, J.; Gong, X.Z.; Wang, L.; Qian, J.P.; Zhang, B.; Garofalo, A.M.; Chen, R.; Jia, G.Z.; Ye, Y.; et al.
Abstract: Significant improvement of plasma performance in high-confinement mode (H-mode) discharges with favourable toroidal field B t, i.e. the ion ∇ B drift towards the primary X-point, has been widely observed in the EAST tokamak with pure radio-frequency heating in contrast to that with the unfavourable B t . Statistical analysis indicates that plasma in the favourable B t has higher core electron temperature, similar core ion temperature and relatively steeper pedestal density compared with that in the unfavourable B t . The improvement in plasma performance is mainly contributed by the increase of core electron temperature in the favourable B t . Further analysis indicates that the plasma with favourable B t has much lower density and recycling in the scrape-off layer (SOL). Lower SOL density and recycling benefit the mitigation of parametric instability activity of lower hybrid wave (LHW), and thus facilitate the increase of core electron temperature in the favourable B t . The performance improvement in the favourable B t demonstrates to be more evident with high LHW power. Divertor local E r × B drift which can increase the backflow particles from the divertor region to the upstream region could be partly responsible for the much higher SOL plasma density in unfavourable B t . These findings could facilitate the application of LHW power on future large fusion devices, such as the China Fusion Engineering Test Reactor, to achieve high-performance steady-state operation.